Potassium channel, ions, and water: simulation studies based on the high resolution X-ray structure of KcsA. - Domene, C; Sansom, MS (2003)
Interactions of Na(+), K(+), Rb(+), and Cs(+) ions within the selectivity filter of a potassium channel have been investigated via multiple molecular dynamics simulations (total simulation time, 48 ns) based on the high resolution structure of KcsA, embedded in a phospholipid bilayer. As in simulations based on a lower resolution structure of KcsA, concerted motions of ions and water within the filter are seen. Despite the use of a higher resolution structure and the inclusion of four buried water molecules thought to stabilize the filter, this region exhibits a significant degree of flexibility. In particular, pronounced distortion of filter occurs if no ions are present within it. The two most readily permeant ions, K(+) and Rb(+), are similar in their interactions with the selectivity filter. In contrast, Na(+) ions tend to distort the filter by binding to a ring of four carbonyl oxygens. The larger Cs(+) ions result in a small degree of expansion of the filter relative to the x-ray structure. Cs(+) ions also appear to interact differently with the gate region of the channel, showing some tendency to bind within a predominantly hydrophobic pocket. The four water molecules buried between the back of the selectivity filter and the remainder of the protein show comparable mobility to the surrounding protein and do not exchange with water molecules within the filter or the central cavity. A preliminary comparison of the use of particle mesh Ewald versus cutoff protocols for the treatment of long-range electrostatics suggests some difference in the kinetics of ion translocation within the filter.